Reading-Based Voice Authentication on a Smartphone: A Case Study of Older Adults - Boonsiri, Jedsada; Chintakovid, Thippaya; Bhumpenpein, Nalinpat (Burapha Science Journal, 2024)
Background and Objectives : Authentication is a vital component of smartphones to protect devices from unauthorized access. Nevertheless, existing schemes are unsuitable for elderly users due to their age-related difficulties. As a result, many older adults employ insecure practices, including disabling device authentication systems. One promising solution is voice authentication, which has been consistently suggested as a more usable option for older adults. However, voice authentication has a drawback regarding vulnerability to an imitation or recording of an enrolled speaker. Among many solutions for this issue, reading-based voice authentication is relatively simple and theoretically usable for older adults. Still, there is insufficient information to confirm the possibility, including older adults’ perceptions and the reactions of Thai subjects toward the system. Therefore, this research intends to confirm that possibility and find whether reading-based voice authentication is usable enough for older adults. Methodology : Three different styles of reading-based voice authentication were developed, and the testing was conducted to evaluate their usability relative to older adults. Participants were divided into three groups for each authentication style. Then, they would use the systems by enrolling and verifying themselves, where the researcher observed their actions and noted their opinions, along with the systems’ performance metrics (Success Rate, Task Time, Error). Main Results : The results of the test were encouraging. In terms of performance, all three styles achieved high task completion rates; almost all participants successfully enrolled in the system and verified themselves. There were significant differences regarding the time needed to complete enrollment. Nonetheless, the verification process used the same amount of time on average. Most errors occurred during the manual voice recording, where participants either forgot to press a button or pressed at the wrong moment. Both the scores from SEQ and SUS questionnaires indicated that all three styles of reading-based voice authentication were easy to use. The statistical tests to compare the results of all three authentication styles indicated that they were comparably usable, and mechanisms, like random passphrases, could be employed without adverse effects on usability. However, the ability to freely choose a passphrase negatively impacts usability as it requires text input and is thus unsuitable for older adults. Most participants expressed positive thoughts about reading-based voice authentication, like the ease of use and convenience. Conclusions : Despite the promising results, this research still has limitations. The number of participants was smaller than intended, which affected the study’s statistical power. Furthermore, this research needs more experiments to compare reading-based voice authentication with other authentication methods, assess its security aspect, and test the system in other settings, such as outdoor locations.